Phenotypic selection of peach cultivars for the tropics - Tadeu, Maraisa Hellen (2017)
The peach tree (Prunus persica) is considered a species of temperate climate, and when cultivated in the tropics modifies its behavior in overcoming dormancy, phenology, production and fruit quality. In this context, the selection of cultivars with a low chilling requirement, high fruit quality and being precocious to take advantage of the seasonality of the market is a challenge for the researcher, as regards the growing in the tropics. However, these characteristics are directly related to the adaptability of this fruit in places of mild weather and its stability in relation to the diversity of the years for cultivation in the tropics. However, it is necessary to know the behavior of different cultivars in the tropics for the success of the productive chain. In this context, the first chapter aimed to select, through multivariate analysis, peach cultivars with greater adaptability and production stability for the tropics. The second chapter proposed to evaluate the duration of phenological stages and to determine the adaptability and stability of the reproductive and vegetative phases of the peaches in the tropics with the objective of optimizing the production system. The third chapter aimed to identify the specific wavelengths provided by light emitting diodes (LEDs) that improve the quality of postharvest peach fruit. The fourth chapter aimed at characterizing and evaluating the influence of different peach cultivars (‘Aurora-1’, ‘Biuti’, ‘Bonão’, ‘Centenário’, ‘Diamante’, ‘Douradão’, ‘Libra’, ‘Régis’ and ‘Tropical’) cultivated in ‘Tropical’ regions on the physical-chemical characteristics, rheological properties and sensory acceptance of the resulting jelly in order to identify the cultivars with the greatest potential for industrial use and to verify which cultivars present a wide range of consumption in the region of Minas Gerais.